Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Smart textile wearables for human-environment interaction - Yuling Chen; Junni Ren; Mingwen Zhang; Dilusha Rajapakse; Fuhao Liu; Byeong Woon Lee; Sang Min Won; Xiaoxiao Zhu (Chemical Engineering Journal, 2026)

Effects of aquatic vegetation on sediment microbial communities and potential nitrogen cycling functions in a shallow lake - Sile Wen; Wangting Yang; Lan Zhou; Yuling Yang; Jinghao Jin; Bingjie Ren; Yuzhi Song; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Coastal marsh conversion to paddy fields leads to a more pronounced stimulation of temperature sensitivity of soil microbial respiration in higher-latitude regions - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Bingjie Ren; Qinan Hu; Lidong Shen (Marine Pollution Bulletin, 2026)

Natural polyphenol-mediated oxidative polymerization and degradation of emerging contaminants - Yangju Li; Hexian Qin; Jiansen Lei; Meimei Wang; Yuling Ren; Dapeng Wu; Haoran Dong (Critical Reviews in Environmental Science and Technology, 2026)

An improved Hydrology-Informed attention LSTM(HIA-LSTM) model for runoff simulation with seasonal snowmelt - Muwu Ling; Yashuo Guan; Yanqing Lian; Xiaonan Sun; Yongliang Gao; Yuling Ren (Journal of Hydrology, 2026)

Breaking acidification-ammonia inhibition cycle in anaerobic co-digestion with alkaline lime mud via synthetic microbial consortium - Linpei Liu; Yao Ren; Xiaoru Chen; Jun Wang; Yuling Huang; Pan Zhang; Qili Zhu; Han Qin; Furong Tan; Mingxiong He; Yong Zhuang (Journal of Environmental Chemical Engineering, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Tryptophan metabolism alterations in neurological and psychiatric diseases: Molecular mechanisms and pharmacological targets - Yuanyuan Wang; Yuling Chen; Hongtao Li; Jingjing Sang; Chen Chen; Lei Xu; Weiting Zhang; Baichen Xiong; Ruijia Jiang; Xinyu Ren; Yao Chen; Haopeng Sun; et al. (Metabolic Brain Disease, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Improving PCR-GLOBWB 2 to model regional water stress dynamics under climate and socioeconomic change scenarios - Yashuo Guan; Yanqing Lian; Muwu Ling; Yongliang Gao; Yuling Ren; Xiaonan Sun (Journal of Hydrology, 2026)

Identifying impact factors of long-term ecological vulnerability using multivariate wavelet coherence analysis - Yuling Ren; Yanqing Lian; Muwu Ling; Saurabh Mishra; Yongliang Gao; Yashuo Guan; Xiaonan Sun (Journal of Hydrology, 2026)

Physicochemical properties, microbial diversity, metabolites and their potential relationships of traditional Chinese Zhacai fermented for different periods - Xinyi Wang; Yuanli Luo; Yuanqing Gu; Ting Ren; Yuling Liu; Xinhui Wang; Nan Zhao; Xin Nie; Dayu Liu; Zhiping Zhao (International Journal of Food Microbiology, 2026)

Revealing the spatial distribution of crown base height across China based on close-range Lidar data - Zekun Yang; Zhiyong Qi; Yuling Chen; Kai Cheng; Haitao Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Yu Ren; Weiyan Liu; Danyang Lin; Guoran Huang; et al. (Remote Sensing of Environment, 2025)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Preparation of omniphobic membrane by anchoring hydrophobic islands at fixed-points for treating hypersaline wastewater - Ronghua Ma; Xiaolong Lu; Jie Gu; Kai Ren; Yuling Ren; Yuefei Song; Zhong Ma (Desalination, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Functionalized smart platforms of ZIF-8: Progress in orthopedic therapeutic applications and challenges - Huaiyuan Zhang; Bohan Ren; Yuling Huang; Xizhou Yao; Yonghua Zhai; Longhai Du (Chemical Engineering Journal, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Novel insights into the morphological effects of trace organic contaminants on water/PhAC selectivity in nanofiltration of sewage - Junhao Zhao; Yanan Wang; Zuqiong Jiang; Yuefei Song; Nan Deng; Yuling Ren; Ronghua Ma; Kai Jiang (Journal of Hazardous Materials, 2025)

Sulfate-mediated enhancement of simultaneous nitrate and hexavalent chromium removal in Fe(0)-based autotrophic bioprocesses - Meng Ren; Chuanjin Xia; Yidan Zhang; Wanying Jia; Mengjiao He; Linfeng Xu; Yuling Zhu (Journal of Environmental Chemical Engineering, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Enhancement of the simultaneous bio-reduction of chromium(VI) and nitrate with a novel solid electron donor: Soluble organics-Fe3O4-Hydrochar prepared with rice husk and Fe(III) ions - Meng Ren; Yidan Zhang; Chuanjin Xia; Weidong Cheng; Yuling Zhu (Chemical Engineering Journal, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Portable aptasensor for smartphones using trimetallic PtPdAuNFs and triplex molecular switch for rapid detection of procymidone - Ruonan Wang; Baoshan He; Zhengyong Liang; Yuling Wang; Huali Jin; Min Wei; Wenjie Ren; Zhiguang Suo; Yiwei Xu (Chemical Engineering Journal, 2025)

Efficient large-scale vegetation mapping at the formation level using multi-source data: A case study in Beijing, China - Jiachen Xu; Yongmei Huang; Kai Cheng; Yi Wang; Tianyu Hu; Hongcan Guan; Yuling Chen; Yu Ren; Mengxi Chen; Zekun Yang; Jiarui Wang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Water stress exacerbated by altered flow pathways in the Tibetan plateau: A critical analysis - Yuling Ren; Saurabh Mishra; Yanqing Lian; Jianyun Zhang; Junliang Jin; Ke Zhang; Weiguang Wang; Yongliang Gao; Yashuo Guan; Muwu Ling; Xiaonan Sun (Environmental Impact Assessment Review, 2025)

Autotrophic Uranium (VI) bioreduction in groundwater by siderite: Comparison with sulfur and zero-valent iron - Yidan Zhang; Meng Ren; Chuanjin Xia; Wenzhong Wang; Yuling Zhu (Environmental Research, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

A self-reinforcing, self-healing, and shape memory polybutadiene-based polyurethane via disulfide bonds for healable flexible sensors - Haolei Shi; Yu Shi; Liping Ren; Wei Zhang; Yuan Ji; Jichi Zhang; Xu Zhong; Yuling Liang; Jidong Dong; Yadong Wu; Wei Li; Dawei Zhang; et al. (Chemical Engineering Journal, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Interface performance and damage strength model of guar gum−treated fiber−reinforcement loess slope protection material - Huaixin Li; Changgen Yan; Jing Ren; Yuling Shi; Han Bao; Zhuolong Jia; Zherui Liang (Journal of Cleaner Production, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Chromium(VI) and nitrate removal from groundwater using biochar-assisted zero valent iron autotrophic bioreduction: Enhancing electron transfer efficiency and reducing EPS accumulation - Chuanjin Xia; Weidong Cheng; Meng Ren; Yuling Zhu (Environmental Pollution, 2025)

Hyperbranched polymer wrapped UIO-66-NH2 as covalent intermediate layer to enhance polyamide membrane for Li+/Mg2+ separation and acid/alkaline stability - Bingbing Yuan; Shuang Yuan; Chaozheng Jia; Ping Hu; Siheng Zhao; Yuling Ren; Meng You; Shengchao Zhao; Kuo Chen; Xiaozhuan Zhang; Dongxiao Yang; Juhui Jiang; et al. (Desalination, 2025)

Spatio-temporal variations in activity of aerobic methane oxidation and community structure of methanotrophs in sediment of Wuxijiang river - Yefan He; Yuling Yang; Hechen Huang; Wangting Yang; Bingjie Ren; Qinan Hu; Jinghao Jin; Sile Wen; Haixiang Cheng; Lidong Shen (Environmental Pollution, 2024)

Highly efficient degradation of ethanol, acetaldehyde, and ethyl acetate removal by bio-trickling filter reactors with various fillers - Hairong Jiang; Yue Wang; Yuling Zhang; Yixuan Yang; Ruoqi Cui; Lianhai Ren; Minglu Zhang; Yongjing Wang (Process Safety and Environmental Protection, 2024)

Microplastics–biofilm in aquatic ecosystem: Formation, pollutants complexation, greenhouse gas emission and ecotoxicology - Saurabh Mishra; Yuling Ren; Xiaonan Sun; Yanqing Lian; Anurag Kumar Singh; Niraj Sharma; K.C. Shikhar (Journal of Environmental Management, 2024)

Activity of anaerobic methane oxidation driven by different electron acceptors and the relative microbiome in paddy fields across various rice growth periods and soil layers - Yuling Yang; Lidong Shen; Caiyu Geng; Bingjie Ren; Yanan Bai; Jinghao Jin; Wangting Yang (Biology and Fertility of Soils, 2024)

Changes in compound temperature and precipitation extremes from combined effects of multiple circulation factors over China - Jingpeng Zhang; Tianbao Zhao; Juanjuan Zhang; Yuling Ren; Zhi Li (Journal of Hydrology, 2024)

Effects of basic amino acids on heterocyclic amines and quality characteristics of fried beef patties at low NaCl level - Pinghua Deng; Shuang Teng; Yu Zhou; Yuling Liu; Boqun Liao; Xiaopu Ren; Yawei Zhang (Meat Science, 2024)

The interplay of soil physicochemical properties, methanogenic diversity, and abundance governs methane production potential in paddy soil subjected to multi-decadal straw incorporation - Yuling Yang; Lidong Shen; Evgenios Agathokleous; Shuwei Wang; Yuhan Jin; Yanan Bai; Wangting Yang; Bingjie Ren; Jinghao Jin; Xu Zhao (Environmental Research, 2024)

Microplastics pollution in the Asian water tower: Source, environmental distribution and proposed mitigation strategy - Saurabh Mishra; Yuling Ren; Xiaonan Sun; Yanqing Lian; Anurag Kumar Singh; Niraj Sharma (Environmental Pollution, 2024)

Distribution, mobilization, risk assessment and source identification of heavy metals and nutrients in surface sediments of three urban-rural rivers after long-term water pollution treatment - Xu Yao; Zheng Wang; Dandan Li; Hejia Sun; Chong Ren; Yilei Yu; Feifei Pei; Yuling Li (Science of The Total Environment, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Heterogeneous variations in wintertime PM2.5 sources, compositions and exposure risks at urban/suburban rural/remote rural areas in the post COVID-19/Clean-Heating period - Zhiyong Li; Zhuangzhuang Ren; Chen Liu; Zhi Ning; Jixiang Liu; Jinming Liu; Zhen Zhai; Xiaohua Ma; Lan Chen; Yuling Zhang; Longkai Bai; Shaofei Kong (Atmospheric Environment, 2024)

Vertical and temporal variations in activity, abundance, and composition of nitrite-driven anaerobic methanotrophs in a paddy field - Caiyu Geng; Lidong Shen; Bingjie Ren; Hechen Huang; Jinghao Jin; Wangting Yang; Evgenios Agathokleous; Jiaqi Liu; Yuling Yang; Yanan Bai; Yuzhi Song (Applied Soil Ecology, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Nitrogen fertilization rate affects communities of ammonia-oxidizing archaea and bacteria in paddy soils across different climatic zones of China - Bingjie Ren; Weiqi Wang; Lidong Shen; Wangting Yang; Yuling Yang; Jinghao Jin; Caiyu Geng (Science of The Total Environment, 2023)

Horizontal and vertical distribution of nitrate-driven anaerobic methane oxidation process in coastal wetlands under different plant species cover across southeast China - Wangting Yang; Weiqi Wang; Lidong Shen; Yanan Bai; Jiaqi Liu; Yuling Yang; Hechen Huang; Bingjie Ren (CATENA, 2023)

Long-term fertilization enhances the activity of anaerobic oxidation of methane coupled to nitrate reduction and associated microbial abundance in paddy soils - Yuling Yang; Lidong Shen; Xu Zhao; Evgenios Agathokleous; Shuwei Wang; Bingjie Ren; Wangting Yang; Jiaqi Liu; Jinghao Jin; Hechen Huang; Hongsheng Wu (Soil Biology and Biochemistry, 2023)

Responses of soil carbon cycling microbial functional genes to nitrogen and phosphorus addition in saline-sodic soils - Xuejun Du; Yanning Ge; Yun Zhang; Hao Hu; Yiying Zhang; Ziye Yang; Xueqin Ren; Shuwen Hu; Haojie Feng; Yuling Song (Plant and Soil, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Performance test and effect evaluation of guar gum-stabilized loess as a sustainable slope protection material - Zhuolong Jia; Changgen Yan; Bo Li; Han Bao; Hengxing Lan; Zherui Liang; Yuling Shi; Jing Ren (Journal of Cleaner Production, 2023)

Larvicidal, acetylcholinesterase inhibitory activities of four essential oils and their constituents against Aedes albopictus, and nanoemulsion preparation - Yuling Li; Weifeng Wu; Rongchao Jian; Xiaofei Ren; Xiaole Chen; Weiqian David Hong; Min Wu; Jinglin Cai; Canyao Lao; Ximing Xu; Zhaojun Sheng (Journal of Pest Science, 2023)

Ameliorative effect of calcium poly(aspartic acid) (PASP-Ca) and calcium poly-γ-glutamic acid (γ-PGA-Ca) on soil acidity in different horizons - Fei Kang; Qilin Lv; Jingbiao Fan; Yun Zhang; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Spatio-temporal variations of activity of nitrate-driven anaerobic oxidation of methane and community structure of Candidatus Methanoperedens-like archaea in sediment of Wuxijiang river - Haixiang Cheng; Yuling Yang; Yefan He; Xugang Zhan; Yan Liu; Zhengfeng Hu; Hechen Huang; Xiaochen Yao; Wangting Yang; Jinghao Jin; Bingjie Ren; Jiaqi Liu; et al. (Chemosphere, 2023)

Effects of abrupt and gradual increase of atmospheric CO2 concentration on methanotrophs in paddy fields - Lidong Shen; Bingjie Ren; Yuhan Jin; Xin Liu; Jinghao Jin; Hechen Huang; Maohui Tian; Wangting Yang; Yuling Yang; Jiaqi Liu; Caiyu Geng; Yanan Bai; et al. (Environmental Research, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Altered microbial P cycling genes drive P availability in soil after afforestation - Ruochen Zhi; Jian Deng; Yuling Xu; Miaoping Xu; Shuohong Zhang; Xinhui Han; Gaihe Yang; Chengjie Ren (Journal of Environmental Management, 2023)

Interaction mechanism between zein and β-lactoglobulin: Insights from multi-spectroscopy and molecular dynamics simulation methods - Chengzhi Liu; Nan Lv; Yuling Song; Lijuan Dong; Min Huang; Qing Shen; Gerui Ren; Ruibo Wu; Binju Wang; Zexing Cao; Hujun Xie (Food Hydrocolloids, 2023)

Projecting extreme climate events in China’s Loess Plateau: multiple RCMs and emission scenarios corrected by a trend-preserving method - Yuling Ren; Jingpeng Zhang; Bingbing Li; Jinxia Fu; Zhi Li (Theoretical and Applied Climatology, 2023)

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Meta-analysis of the effect of the overexpression of aquaporin family genes on the drought stress response - Jianhong Ren; Xiaoxiao Yang; Chunying Ma; Yuling Wang; Juan Zhao; Le Kang (Plant Biotechnology Reports, 2021)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Ectopic expression of the maize ZmADF3 gene in Arabidopsis revealing its functions in kernel development - Dahe Qiao; Yongbin Dong; Long Zhang; Qiang Zhou; Chunhui Hu; Yangliu Ren; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Calcium regulates glutamate dehydrogenase and poly-γ-glutamic acid synthesis in Bacillus natto - Yonghong Meng; Guiru Dong; Chen Zhang; Yuanyuan Ren; Yuling Qu; Weifeng Chen (Biotechnology Letters, 2016)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Genetic and genotype × environment interaction effects analysis for erucic acid content in rapeseed (Brassica napus L.) - Chunhai Shi; Haizhen Zhang; Jianguo Wu; Changtao Li; Yuling Ren (Euphytica, 2003)